Use of Hormone Therapy in Women with Early Menopause and Premature Ovarian Insufficiency - Lersten, Ivy; Clain, Elizabeth; Santoro, Nanette (Seminars in Reproductive Medicine, 2020)
Women with early menopause or primary ovarian insufficiency (POI) experience a menopausal state a decade or more earlier than their peers. The health consequences for POI are vast and varied with detrimental effects seen on neurological, psychological, bone, and cardiovascular systems. The risk profile of POI patients requires special attention, as they differ from a typical menopausal population. This review will explore the health risks associated with POI and examine the various treatment options and also the risks associated with hormone therapy. Given the risks and benefits, POI patients should be strongly encouraged to start hormone therapy until the median age of menopause.
Keywords: premature menopause; early menopause; primary ovarian insufficiency; hormone therapy